White Reconstruction : Domestic Warfare and the Logics of Genocide - Rodriguez, Dylan (Book collections on Project MUSE., 2020)
We are in the fray of another signature moment in the long history of the United States as a project of anti-Black and racial-colonial violence. Long before (and well after) November 2016, white nationalism, white terrorism, and white fascist statecraft proliferated state and extra-state terror as a common order. Here, Dylan Rodríguez counter-narrates the long "post-civil rights" half-century as a period of White Reconstruction, in which the struggle to reassemble the ascendancy of White Being toxifies the formal disassembly of U.S. (Jim/Jane Crow) apartheid and permeates the political and institutional logics of diversity, inclusion, formal equality, and "multiculturalist white supremacy." Thinking across a variety of archival, testimonial, visual, and activist texts--from Freedmen's Bureau documents and the "Join LAPD" hiring campaign to Barry Goldwater's hidden tattoo and the Pelican Bay prison strike--White Reconstruction implicates the cultural politics and statecraft of white liberalism and reaction alike, illustrating how anti-Black and racial-colonial domestic war not only survive periods of reform but are the conditions of dominance on which such reforms rely, and through which they often articulate. Throughout White Reconstruction, Rodríguez considers how the creative, imaginative, speculative collective labor of abolitionist praxis responds to legitimated and normalized state violence and terror, showing how the complex and constructive work of abolition can displace and potentially destroy the ascendancy of White Being and Civilization in order to create possibilities for insurgent thriving.